The Application of Restorative Justice In The Settlement of Traffic Accident Cases (A Case Study In The Jurisdiction of The Bekasi City Resort Police) - Chairunnisa, Nurriva; Hendriana, Rani; Retnaningrum, Dwi Hapsari; Prakash Nunna, Bhanu (Jurnal Hukum In Concreto, 2024)
Indonesian National Police Regulation Number 8 of 2021 regarding Criminal Case Handling based on Restorative Justice serves as the legal basis, empowering the police to resolve cases by applying Restorative Justice principles. This research aims to examine the implementation and inhibiting factors of Restorative Justice in resolving traffic accident cases in the jurisdiction of Bekasi City Police Resort. This study employs an empirical juridical approach with descriptive-analytical research specifications. The research location is conducted at Bekasi City Police Resort. The research findings indicate that firstly, Bekasi City Police Resort undertakes several stages in resolving cases through Restorative Justice, namely the attempt stage of mediation, the stage of requesting cessation of legal proceedings with Restorative, and the stage of determining the Letter of Termination of Investigation (SP3). Secondly, the research results show several obstacles in applying Restorative Justice to traffic accident cases in Bekasi City Police Resort, namely the substantive component. There are also other inhibiting factors, such as the victim party demanding a relatively high amount of compensation. In contrast, the perpetrator party cannot pay the total amount, failing the peace agreement.